A study on hydrocarbon resins as an advanced material for performance enhancement of radial passenger tyre tread compound. Issue 15 (19th November 2021) - Shee, Biswajit; Chanda, Jagannath; Dasgupta, Mridul; Sen, Amit Kumar; Bhattacharyya, Sanjay Kumar; Das Gupta, Saikat; Mukhopadhyay, Rabindra
Abstract: Advancement in radial passenger car tyre tread compound introduces performance resin as a potential ingredient to improve wet grip (WG) and rolling resistance (RR). In this direction, our approach is to investigate the effect of two types of performance resins as Resin‐1 (mixture of aliphatic and aromatic) and Resin‐2 (aliphatic hydrocarbon) in silica filled solution polymerized styrene butadiene rubber (SSBR)/butadiene rubber (BR) based tread cap compound. Resin‐1 and Resin‐2 replaced low poly cyclic aromatic (PCA) oil by 10 phr (partially) and 20 phr (completely) with respect to the reference compound. It was observed that Resin‐1 has improved WG by 18% and 52%, whereas Resin‐2 showed 33% and 54% improvement at 10 phr and 20 phr replacement, respectively. Microscopic analysis was carried out to identify the dispersion of silica after replacement of oil by resins. Abrasion and fatigue resistance were studied by Laboratory Abrasion Tester (LAT‐100) and Tear Fatigue Analyzer (TFA) to understand the wear and fracture behavior of the modified compounds. Resin‐2 displayed 54% improvements in WG keeping similar RR and fatigue resistance by complete replacement of oil, whereas partial replacement was not appreciated due to less impact in dynamic mechanical properties. Abstract :